Efficient Detection of DNA Polymorphisms by Fluorescent RAPD Analysis - Graham E. Corley-Smith; Chinten James Lim; Gabriel B. Kalmar; Bruce P. Brandhorst (BioTechniques)
A method is presented for the analysis of fluorescently labeled random amplified polymorphic DNA (FRAPD) fragments. A DNA sequencer and collection and analysis software were used to estimate the sizes of DNA fragments based on their mobilities relative to in-lane size markers. This allowed confident identification and comparison of FRAPD markers both within and between polyacrylamide gels. In comparison with analysis of RAPD products using ethidium bromide-stained agarose gels, fluorescent analysis improved the sensitivity, resolution and precision of sizing of RAPD products of about 50–2100 bp. FRAPD fragments produced from amplification of zebrafish DNA are informative as genetic markers that segregate with Mendelian inheritance. FRAPD analysis was found to be very efficient for identifying new DNA polymorphisms.